2017
DOI: 10.1016/j.bjorl.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Hearing performance as a predictor of postural recovery in cochlear implant users

Abstract: The CI users with good hearing performance had a higher index of postural recovery when compared to CI users with poor hearing performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Recently, it was shown that postural recovery was reduced in CI recipients with poor hearing performance as compared with good CI recipients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that postural recovery was reduced in CI recipients with poor hearing performance as compared with good CI recipients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…HI children exhibit worse gait performance than NH children, with abnormal ground reaction forces, higher propulsion and lower free movements [13,14]. Higher hearing impairment determines worse postural recovery and gait performance [14,15] and hearing aids and cochlear implants may help promote improvements in gait and stability during walking [16]. …”
Section: Introductionmentioning
confidence: 99%
“…The auditory performance was evaluated as a predictor of postural control and compared among users of CI with good auditory performance with auditory performance unsatisfactory and with CI performed with at least six months after the surgery, by means of tests of Dynamic Posturography (CDP) of sensory organization (TOS) and adaptation (TAd), with the aim of assessing the learning ability, in the short term, in postural recovery strategies. CI users, with good auditory performance, had a higher incidence of postural recovery, when compared to CI users with unsatisfactory auditory performance 32 .…”
Section: Literature Reviewmentioning
confidence: 87%